Three new abietane-type diterpenes from the bark of Cryptomeria japonica. (March 2017) - Chang, Chi-I; Chen, Chien-Chih; Wang, Sheng-Yang; Chang, Hsun-Shuo; Chao, Louis Kuoping; Chen, Jih-Jung; Chen, Cheng-Chi; Kuo, Yueh-Hsiung
Graphical abstract: Highlights: Three new abietane-type diterpenoids were isolated from Cryptomeria japonica . The structures of isolates were elucidated by spectroscopic methods. The abietane-6, 7-diols could be the precursors for the family of taiwaniaquinoids. Abstract: Three new abietane-type diterpenoids, 7α-butoxyabieta-8, 12-diene-11, 14-dione (1 ), 6α, 7α-dihydroxyabieta-8, 12-dien-11, 14-dione (2 ), and 6α, 7β-dihydroxyabieta- 8, 12-diene-11, 14-dione (3 ) were isolated from the bark of Cryptomeria japonica D. Don. Their structures were established by means of 1D and 2D NMR, IR, UV, and HR-EI-MS spectra and comparison with the data of known analogues.